2014
DOI: 10.4330/wjc.v6.i6.449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conditioning hyperglycemic on myocardial infarction rats: Cardiac cell survival factors

Abstract: in diabetic animals leads to increased capillary density before myocardial infarction. Despite poor prognostic in the long-term, all these results suggest that diabetes mellitus and consequently hyperglycemia may indeed play a cardioprotective role against myocardial infarction in the short term.© 2014 Baishideng Publishing Group Inc. All rights reserved.Key words: Conditioned hyperglycemia; Diabetes mellitus; Myocardial infarction; Cardioprotection; Survival factors Core tip: Hyperglycemia or diabetes trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Malfitano et al [ 40 ] and Egorova et al [ 41 ] have found that the increase in glucose availability, the preferred energetic substrate for the heart in stress condition, is likely to play a key cardioprotective role under ischemia. Diabetes promotes a marked increase in plasma glucose and free fatty acid levels, thus increasing the availability of these metabolites to tissues and organs, including the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Malfitano et al [ 40 ] and Egorova et al [ 41 ] have found that the increase in glucose availability, the preferred energetic substrate for the heart in stress condition, is likely to play a key cardioprotective role under ischemia. Diabetes promotes a marked increase in plasma glucose and free fatty acid levels, thus increasing the availability of these metabolites to tissues and organs, including the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, capillary density may effectively contribute to the reduction of ischemic injury and cardiac fibrosis in diabetic animals. These alterations might play an important role in improving heart function and increasing glucose transporter type 1 expression, which in turn may be critical for glucose uptake in ischemic conditions in diabetic infarcted rats [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the ischemic hearts from the mildly diabetic animals are resistant to ischemia [ 8 ], and the severely diabetic hearts are more prone to ischemic injury [ 9 ]. Several mechanisms have been proposed to explain the cardioprotective property of a high glucose exposure, by an increase in survival pathways, such as antiapoptotic factor Bcl-2, and prosurvival factors such as protein kinase B (Akt), the inactivation of the proapoptotic factor bad, inappropriate expression of proangiogenic vascular endothelial growth factor (VEGF), hypoxia inducible factor 1 α , and protein kinase C- ε [ 10 ].…”
Section: Introductionmentioning
confidence: 99%